In vivo quantification of the 3D kinematics and coupling of the thumb base joints. (August 2022) - Sciacca, D.; D'Agostino, P.; Vanneste, M.; Kerkhof, F.; Vereecke, EE.
Highlights: This study provides valuable information on the in vivo 3D kinematics of the radioscaphoid (RS), scaphotrapezial (ST) and trapeziometacarpal (TMC) joints during thumb movement in healthy subjects. Strong inter-joint coupling was found between the RS and ST joints during thumb extension and abduction. Image-based quantification of kinematics is an accurate approach to study complex joint systems such as the thumb base. Baseline 3D kinematics of the thumb base joints can aid our understanding of motion deficits resulting from joint disorders. Abstract: Full thumb mobility is required to execute tasks of daily living and results from the combined motions of the thumb joints. In this study, we focus on the coupling between the proximal joints of the thumb, the radioscaphoid (RS), scaphotrapezial (ST) and trapeziometacarpal (TMC) joints. We quantified the 3D kinematics of these joints during maximal thumb extension and abduction in a group of healthy volunteers using an image-based technique. Semi-dynamic CT scans of the dominant hand of 36 healthy subjects with the thumb in different standardized positions were used. The maximal range of motion of each joint in the different planes was calculated using a markerless bone registration method. Inter-joint coupling was assessed by performing a regression analysis between the range of motion of the joints during both thumb movements. Strong inter-joint coupling was found between the RS and ST joints during thumb extension and abduction, whereas coupling between the other joints was moderate to weak. This study provides valuable information on the in vivo 3D kinematics of the RS, ST and TMC joints during thumb movement. This can be used as input for modeling studies, where the coupling between the joints can decrease the degrees of freedom of the model. Moreover, these baseline data of a healthy cohort can be used for comparison with the kinematics of patients with TMC osteoarthritis or other pathologies and aid our understanding of motion deficits resulting from these joint disorders.